2021
DOI: 10.1175/jhm-d-20-0147.1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Snow Gauge Collection Efficiency through a Knowledge of Solid Precipitation Fall Speed

Abstract: The collection efficiency (CE) of a typical gauge-shield configuration decreases with increasing wind speed, with a high scatter for a given wind speed. The scatter in the CE for a given wind speed arises in part from the variability in the characteristics of falling snow and atmospheric turbulence. This study uses weighing gauge data collected at the Marshall Field Site near Boulder, Colorado during the WMO Solid Precipitation InterComparison Experiment (SPICE) to show that the scatter in the collection effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…This result was later confirmed by Leroux et al. (2021) and Hoover et al. (2021), who found a dependence of the undercatch bias on the hydrometeor fall velocity, being the fall velocity in the atmosphere basically controlled by the size (and shape) of the falling particles, therefore by the PI itself.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…This result was later confirmed by Leroux et al. (2021) and Hoover et al. (2021), who found a dependence of the undercatch bias on the hydrometeor fall velocity, being the fall velocity in the atmosphere basically controlled by the size (and shape) of the falling particles, therefore by the PI itself.…”
Section: Introductionsupporting
confidence: 53%
“…More recently, the physical dependence of the undercatch bias on the measured PI was demonstrated by Colli et al (2020) for solid precipitation and by for liquid precipitation. This result was later confirmed by Leroux et al (2021) and Hoover et al (2021), who found a dependence of the undercatch bias on the hydrometeor fall velocity, being the fall velocity in the atmosphere basically controlled by the size (and shape) of the falling particles, therefore by the PI itself.…”
supporting
confidence: 53%
“…For example, X-ray tomography can measure the porosity and specific surface area of snow samples, ignoring the fact that significant differences in the morphology of snow crystals also affect their physical properties [29]. Laser raindrop spectrometry can only measure the size of snow crystals falling naturally but cannot observe the metamorphic process of snow in the long term [30]. A uniform standard for defining snow crystal shape parameters is currently nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…The wind-induced bias of precipitation measurements obtained using catching type gauges dependsfurther than the instrument geometry and the wind speedon the size of individual particles and the associated fall velocity (Leroux et al, 2021). Meickle (1819) and Jevons (1861) were the first authors to highlight the aerodynamic behaviour of precipitation measurement instruments.…”
Section: Introductionmentioning
confidence: 99%